Single Neutralizing Monoclonal Antibodies Targeting the VP1 GH Loop of Enterovirus 71 Inhibit both Virus Attachment and Internalization during Viral Entry - Ku, Zhiqiang (J Virol, 2015)
Antibodies play a critical role in immunity against enterovirus 71 (EV71). However, how EV71-specific antibodies neutralize infections remains poorly understood. Here we report the working mechanism for a group of three monoclonal antibodies (MAbs) that potently neutralize EV71. We found that these three MAbs (termed D5, H7, and C4, respectively) recognize the same conserved neutralizing epitope within the VP1 GH loop of EV71. Single MAbs in this group, exemplified by D5, could inhibit EV71 infection in cell cultures at both the pre- and postattachment stages in a cell type-independent manner. Specifically, MAb treatment resulted in the blockade of multiple steps of EV71 entry, including virus attachment, internalization, and subsequent uncoating and RNA release. Furthermore, we show that the D5 and C4 antibodies can interfere with EV71 binding to its key receptors, including heparan sulfate, SCARB2, and PSGL-1, thus providing a possible explanation for the observed multi-inhibitory function of the MAbs. Collectively, our study unravels the mechanism of neutralization by a unique group of anti-EV71 MAbs targeting the conserved VP1 GH loop. The findings should enhance our understanding of MAb-mediated immunity against enterovirus infections and accelerate the development of MAb-based anti-EV71 therapeutic drugs. IMPORTANCE Enterovirus 71 (EV71) is a major causative agent of hand, foot, and mouth disease (HFMD), which has caused significant morbidities and mortalities in young children. Neither a vaccine nor an antiviral drug is available. Neutralizing antibodies are major protective components in EV71 immunity. Here, we unraveled an unusual mechanism of EV71 neutralization by a group of three neutralizing monoclonal antibodies (MAbs). All of these MAbs bound the same conserved epitope located at the VP1 GH loop of EV71. Interestingly, mechanistic studies showed that single antibodies in this MAb group could block EV71 attachment and internalization during the viral entry process and interfere with EV71 binding to heparan sulfate, SCARB2, and PSGL-1 molecules, which are key receptors involved in different steps of EV71 entry. Our findings greatly enhance the understanding of the interplays among EV71, neutralizing antibodies, and host receptors, which in turn should facilitate the development of an MAb-based anti-EV71 therapy.